3.3: Single Mirror IMOD Display for Practical Wearable Device. Issue 1 (June 2015) - Chang, Tallis; Chan, Edward; Hong, John; Kim, Cheonhong; Ma, Jian; Pan, Yaoling; Van Lier, Rob; Wen, Bing; Zhou, Lixia; Mulabagal, Pavan
Abstract : We present the progress toward realizing commercially viable wearable displays that will enable always‐on operation using Single Mirror IMOD (SMI), a continuously tunable reflective color display technology based on interferometric modulation (IMOD).